2015
DOI: 10.1016/j.ydbio.2014.10.023
|View full text |Cite
|
Sign up to set email alerts
|

Ptch2 shares overlapping functions with Ptch1 in Smo regulation and limb development

Abstract: Ptch1 and Ptch2 are highly conserved vertebrate homologs of Drosophila ptc, the receptor of the Hedgehog (Hh) signaling pathway. The vertebrate Ptch1 gene encodes a potent tumor suppressor and is well established for its role in embryonic development. In contrast, Ptch2 is poorly characterized and dispensable for embryogenesis. In flies and mice, ptc/Ptch1 controls Hh signaling through the regulation of Smoothened (Smo). In addition, Hh pathway activation also up-regulates ptc/Ptch1 expression to restrict the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 60 publications
2
32
0
Order By: Relevance
“…We reasoned that genetic ablation of both Ptch1 and Ptch2 would be necessary to assess non-cell autonomous Smo regulation in these cells because Ptch2 compensates for Ptch1 loss in cell autonomous Smo regulation (Alfaro et al, 2014; Zhulyn et al, 2015). We previously reported that the Hh pathway in Ptch1 LacZ/LacZ ; Ptch2 -/- nEBs could not be further activated by the Smo agonist SAG (Chen et al, 2002b), suggesting maximal Smo activation in the absence of Ptch1/2.…”
Section: Resultsmentioning
confidence: 99%
“…We reasoned that genetic ablation of both Ptch1 and Ptch2 would be necessary to assess non-cell autonomous Smo regulation in these cells because Ptch2 compensates for Ptch1 loss in cell autonomous Smo regulation (Alfaro et al, 2014; Zhulyn et al, 2015). We previously reported that the Hh pathway in Ptch1 LacZ/LacZ ; Ptch2 -/- nEBs could not be further activated by the Smo agonist SAG (Chen et al, 2002b), suggesting maximal Smo activation in the absence of Ptch1/2.…”
Section: Resultsmentioning
confidence: 99%
“…We used Ptch1 −/− cells to avoid interference by endogenous Ptch1, which is reported to homomultimerize (22). These cells do not express the Patched ortholog, Ptch2 ; and therefore, Ptch1 is the Hh receptor responsible for Smo regulation and control of Hh pathway activity in these cells (23, 24). …”
Section: Resultsmentioning
confidence: 99%
“…However, Ptch2 appears to have a distinct downstream signaling role from Ptch1, as it is expressed at much higher levels in specific organs such as testis and ovary (O’Hara et al, 2011). In the absence of ligand binding, Ptch2 has a decreased ability to inhibit the activity of Smo, compared with Ptch1 (Alfaro et al, 2014; Zhulyn et al, 2015). Structurally, Ptch protein has a sterol sensing domain (SSD), which is essential for inhibiting the activity of Smo (Lindstrom et al, 2006).…”
Section: Sonic Hedgehog Signaling: Components Routes and Mechanismmentioning
confidence: 95%